2011
DOI: 10.1186/1748-717x-6-89
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile-associated diarrhea in radiooncology: an underestimated problem for the feasibility of the radiooncological treatment?

Abstract: Background and PurposeOver the last years an increasing incidence of Clostridium difficile-associated diarrhea (CDAD) has been reported. Especially haematology-oncology patients are at risk of developing CDAD.The aim of this analysis is to determine the incidence of CDAD in radiooncological patients and to find out what relevance CDAD has for the feasibility of the radiooncological treatment, as well as to detect and describe risk factors.Patients and MethodsIn a retrospective analysis from 2006 to 2010 34 hos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 45 publications
(68 reference statements)
1
20
0
1
Order By: Relevance
“…Mortality/fatality rates as high as 26% have been reported in old and very old patients, and patients with underlying disease like progressive solid tumours. Especially haematology-oncology patients, having systemic diseases and receiving high dose chemotherapy, are at risk for CDI (Hautmann et al, 2011). Both the recurrence and overgrowth after initial dysbiosis can be partly explained by spore forming ability, specific adhesions in the colon and hypervirulent strains via additional production of a binary toxin.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mortality/fatality rates as high as 26% have been reported in old and very old patients, and patients with underlying disease like progressive solid tumours. Especially haematology-oncology patients, having systemic diseases and receiving high dose chemotherapy, are at risk for CDI (Hautmann et al, 2011). Both the recurrence and overgrowth after initial dysbiosis can be partly explained by spore forming ability, specific adhesions in the colon and hypervirulent strains via additional production of a binary toxin.…”
Section: Discussionmentioning
confidence: 99%
“…The cost per case ranges from approx. 2,500 USD (total cost estimate 3.5 billion) to 4,000 USD in the UK (Hickson, 2011), with health care system costs between 5,000 (USA) and 8,000 (EU) USD per primary episode and almost 14,000 USD for a case of recurrent CDI (Hautmann et al, 2011) with a total burden worldwide in the tens of billions. All available data show that CDI is much more difficult to prevent and cure than ordinary diarrhoea.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hautmann et al noted that radio-oncological patients were also patients at risk of C. difficile infection and that the incidence was 1.6%, especially for head and neck cancer patients 8. Prendergast et al reported that irradiation-associated reductions in normal beef surface flora influenced survival of nonpathogenic Escherichia coli and pathogenic E. coli , suggesting that irradiation may affect the chemical or physical composition of flora 9.…”
Section: Discussionmentioning
confidence: 99%